Methodology for Estimating the Expected Cost of Engineering and Technology Innovation - T. N. Saurenko; E. G. Anisimov; E. S. Rodionova (Управленческое консультирование)
The article proposes a methodology for estimating the expected cost of technical and technological innovations. The evaluation is performed in the pre-design phase of the innovation (project initiation phase). It relies on the method of analogy and is implemented based on the principle of “so was - so will be.” At the same time, the available analogues provide objective information about “how it was.” Extending this data into the future to estimate the cost of design relies on probabilistic interpretation of the available uncertainty. Uncertainty removal is accomplished using the principle of maximum entropy. This ensures the most complete consideration of the available objective information and minimizes speculation in assessing the cost of designing innovative objects. In general, the methodology proposed in the article allows obtaining objective estimates of the expected cost of designing technical and technological innovations in the standard information situation for the initiation stage of the project.